Biblioteki i bibliotekarze w przestrzeni filmowej (reprezentacje i konotacje) - Gierszewska, Barbara Lena (Przestrzenie Teorii, 2019)
Gierszewska Barbara Lena, Biblioteki i bibliotekarze w przestrzeni filmowej (reprezentacje i konotacje) [Libraries and Librarians in the Film Space (Representations and Connotations)]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 213–238. ISSN 1644-6763. DOI 10.14746/pt.2019.32.11. Using selected films, a picture of library buildings and their interiors from the 1950s to the present day has been created. The vast majority of libraries are “temples of knowledge”, and librarians (invariably educated and relatively unattractive women) are the “guardians” of the collections. Contemporary film rarely depicts shows libraries as a system not to be overestimated “in the times of smart phones and social media”. Filmmakers’ attention is drawn mainly the interesting architecture of library interiors to, in which “library scenes” are set, hence the aura of library is seldom perceptible. Książnice is often the backdrop or part of the story told in the film, and sometimes reveal other features such as the genre and other books important to the characters.